2011
DOI: 10.1080/10410236.2010.546771
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Loneliness, Recuperative Processes, and Their Direct and Indirect Effects on Health

Abstract: This study tested predictions that potentially explain why social support is associated with better health and loneliness is associated with poorer health. Social support was predicted to be associated with better health because it minimizes loneliness, which itself is associated with poor health. In particular, this study evaluated the role of recuperative processes, namely, sleep and leisure, in the association between loneliness and poor health. Participants were 224 adults aged 18-81 years who completed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 52 publications
6
70
0
5
Order By: Relevance
“…This research supports the link between social support and positive health outcomes proposed by the Theory of Reasoned Action and other researchers [16][17][18]. Long-term follow-up of walking behavior after the structured walking exercise might be considered in future studies.…”
Section: Walkingmentioning
confidence: 48%
See 1 more Smart Citation
“…This research supports the link between social support and positive health outcomes proposed by the Theory of Reasoned Action and other researchers [16][17][18]. Long-term follow-up of walking behavior after the structured walking exercise might be considered in future studies.…”
Section: Walkingmentioning
confidence: 48%
“…The Theory of Reasoned Action and other research findings have confirmed a link between social support and positive health outcomes [16][17][18]. Adults with larger social support systems had higher levels of self-esteem and exercise behavior than those with lower social support [19].…”
mentioning
confidence: 86%
“…Kod starih osoba koje nisu usamljene ne postoji povezanost između toga kako one subjektivno procenjuju sopstveno zdravlje i koliko su zadovoljne životom. Ovakvi nalazi su u saglasnosti sa brojnim empirijskim nalazima koji ukazuju na štetnost koju usamljenost ostvaruje kako po zdravlje tako i po blagostanje osoba u starosti (Buchman et al, 2009;Hawkley et al, 2010;Segrin & Domschke, 2011;Wenger et al, 1996). Pretpostavljeni mehanizam putem koga se povišena usamljenost negativno odražava na relaciju zdravlja i blagostanja jeste povišeni nivo stresa, koji je povezan i sa visokom usamljenošću i sa generalnim zdravljem (Hawkley & Cacioppo, 2007).…”
Section: Diskusijaunclassified
“…Stek et al, 2005). Studije posvećene relaciji između socijalne umreženosti i zdravstvenog statusa starih ukazale su na značajnu povezanost između usamljenosti i inflamatornog statusa i nesanice (Cacioppo, Hawkley, Norman, & Berntson, 2011), kardiovaskularnih bolesti (Hawkley, Thisted, Masi, & Cacioppo, 2010), osiromašene motorike (Buchman et al, 2009), ali i nepridržavanja lekarskih uputa tokom medicinske terapije (Segrin & Domschke, 2011). Jedan broj studija ukazuje da se ova veza između usamljenosti i zdravlja može objasniti činjenicom da usamljeni ljudi generalno manje vode računa o zdravstvenom ponašanju i slabije spavaju (Cacioppo et al, 2002) kao i da doživljavaju više stresa (McHugh & Lawlor, 2013) i osećaju pad životnog elana (Eng, Rimm, Fitzmaurice, & Kawachi, 2002).…”
unclassified
“…In addition to depression, loneliness has also been linked to stress, poor sleep quality, alcoholism, and reduced physical activity (Akerlind & Hornquist, 1992;Hawkley, Thisted, & Cacioppo, 2009;Segrin & Domschke, 2011;Segrin & Passalacqua, 2010). This set of negative consequences does not take place in a vacuum.…”
Section: Lonelinessmentioning
confidence: 99%